General and disease-specific pain trajectories as predictors of social and political outcomes in arthritis and cancer - James, Richard J.E.; Walsh, David A.; Ferguson, Eamonn (BioMed Central, 2018)
Background: While the heterogeniety of pain progression has been studied in chronic diseases, it is unclear the extent to which patterns of pain progression among people in general as well as across different diseases impacts on social, civic and political engagement. We explore these issues for the first time. Methods: Using data from the English Longitudinal Study of Ageing, latent class growth models were used to estimate trajectories of self-reported pain in the entire cohort, and within subsamples reporting diagnoses of arthritis and cancer. These were compared at baseline on physical health (e.g., BMI, smoking) and over time on social, civic and political engagement.